Rhetorical stages and linguistic resources in the writing of research methods: a genre-based study of TESL research articles - Jason Miin-Hwa Lim (Universiti Malaysia Sabah, 2009)
This is a genre-based investigation into the Methodls sections of 32 research articles on the teaching of English as a second language (TESL). which have been written by expert writers and published in eight well-established international refereed journals. The project is of considerable significance and relevance to a large number of university students and academicians in the field of TESL as it has yielded important findings on how the Method/s sections of research reports can be appropriately written to meet the expectations of various members of an academic research community, including dissertation examiners, reviewers, and supervisors. This study is also of great importance in that the findings may be put to effective use in the teaching of English for research purposes (ERP) at tertiary level. The genre analysis is necessary as the existing teaching materials which deal with the English language used in research articles, are insufficient in providing information on how research methods should be systematically and logically presented using appropriate linguistic choices. On the basis of Swales' (1990; 2004) move analysis, the researcher has conducted (i) a detailed quantitative analysis of the rhetorical moves and steps using the Statistical Package for Social Sciences (SPSS), and (ii) a more thorough qualitative analysis of the language resources employed in each of the 11 constituents steps found in the corpus. Given that the research papers in the field of TESL consist of communicative functions and linguistic choices which differ considerably from those in other disciplines, the findings of this study have provided valuable insights into how the Method sections of TESL articles can be presented using different rhetorical moves and steps, and how specific linguistic mechanisms can be employed to meet the communicative intentions concerned.